INTERNALISASI AKUNTANSI MANAJEMEN PERSPEKTIF BALANCE SCORECARD DALAM PENGUKURAN KINERJA PERGURUAN TINGGI - Adam, Helmy (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Performance measurement and universities in Indonesia is still considered very limited in terms of looking at the concept of higher education as an integral entity in the process of education and operations activities.Â UsingÂ four of Balanced Scorecard perspectives (financial, internal business processes, learning and growth, and customer) in developing performance measurement tools for management accountants in addition to do with strategic mission could theoretically be developed in college. Four perspective is revealed in some technical measures that will be described in this paper although some integral untested empirically.Keywords: Internalisasi, perspektif, kinerja, nirlaba